First‐trimester sonographic diagnosis of sirenomelia: A multicenter series of 12 cases and review of the literature. (4th March 2020) - Sepulveda, Waldo; Bornstein, Eran; Andreeva, Elena; Montano, Ignacio; Gutierrez, Jorge; Martinez‐Ten, Pilar; Meagher, Simon
Abstract: Objective: To determine the key sonographic features for the diagnosis of sirenomelia in the first trimester of pregnancy. Methods: Cases of sirenomelia from several prenatal diagnosis centers were retrospectively identified and reviewed. The diagnosis was established through the detection of fused lower limbs. Additional sonographic findings were also noted. Results: A total of 12 cases were collected. The most striking sonographic finding was the detection of malformed lower limbs, which appeared to be fused and in an atypical position. Nuchal translucency thickness was mildly increased in three cases (25%). An abdominal cyst, representing the dilated blind‐ending bowel, was noted in seven cases (58%). Color flow imaging detected a single umbilical artery in six cases (50%) and the associated intra‐abdominal vascular anomalies in three cases (25%). No cases of aneuploidy were detected. The pregnancy was terminated in nine cases (75%) and intrauterine demise occurred in the remaining three cases (25%). Conclusions: The sonographic detection of abnormal lower limbs or an intra‐abdominal cyst located laterally during the first‐trimester scan may be warning signs of sirenomelia. This should prompt a detailed examination of the fetal lower body and intra‐abdominal anatomy, including the main abdominal vessels, in order to look for additional confirmatory findings.